Patient’s perspective about the photographs taken during the orthodontic therapy for documentation - MANOHARAN, SUHAS; VARGHESE, REMMIYA MARY; KUMAR. S, ARAVIND (The journal of contemporary issues in business and government, 2020)
Clinical Photography is an important requirement for better clinical diagnosis, treatment planning and case documentation in modern Orthodontics.The primary purpose of dental photography is clinical recording of intra oral and extra oral manifestations. Other secondary uses may be marketing , education , communication, dento legal documentation. Dental photography also improves the quality of care provided and overall status of a dental practice. Main purpose of dental photography in orthodontics is documentation for explaining and demonstrating various stages and processes involved in a treatment and to assess the treatment progress. Till date there are no existing surveys on dental photography from a patient’s perspective. A cross-sectional questionnaire study was conducted among the patients undergoing orthodontic therapy .The sample size of 300 patients were selected. A close ended questionnaire was used to assess the patient perspective about the dental photographs taken during the orthodontic therapy. A survey software was used to reduce sampling bias.Repeated answers or questioning were avoided. All patients undergoing fixed orthodontic treatment were included in the study. Chi-square tests are applied to find the association between the parameters and the level of significance.Patient satisfaction and comfort is of utmost importance. Hence changes in the design can be brought about in retractors or mirrors to improve the comfort of the patient during clinical photography. Within the limits of the study, the result of the study has shown that there was positive experience regarding dental photography for orthodontic purposes from the majority of the patients.